Short- and Long-Term Poverty and Social Policy in a 'Snakes and Ladders' Model of Growth - Cuevas, Alfredo (IMF Working Papers; Working Paper ;, 2001)
Throughout the world, the great popularity of programs to protect those who may fall into poverty stands in contrast with the weakness of policies aimed at helping individuals who are already poor to overcome long-term poverty. In the paper, an OLG model with persistent poverty and limited social mobility is used to explore some of the reasons for the different success rates of these two types of policies, as well as the gains that can be expected from these and other policies in terms of economic growth. The popularity of social insurance schemes may be due to their relative ex-ante fairness, while the reluctance of societies to support effective policies to reduce long-term poverty may be explained by the redistributive bias of these policies, especially in the short term. However, the failure to attack long-term poverty can reduce long-run growth.